Air pollution is associated with the development of atherosclerosis via the cooperation of CD36 and NLRP3 inflammasome in ApoE-/- mice. (15th June 2018) - Du, Xihao; Jiang, Shuo; Zeng, Xuejiao; Zhang, Jia; Pan, Kun; Zhou, Ji; Xie, Yuquan; Kan, Haidong; Song, Weimin; Sun, Qinghua; Zhao, Jinzhuo
Graphical abstract: Highlights: Shanghai-METAS used in this study was the first comprehensive animal exposure system which were established in China. This study was the first to use the Shanghai-METAS to explore the potential mechanism of PM2.5- induced atherosclerosis. The cooperation of CD36 and NLRP3 inflammasome activation may be the potential mechanism linking PM2.5 and atherosclerosis. Abstract: Previous studies have indicated that the main air pollutant fine particulate matter (≤2.5 μm; PM2.5 ) exposure is associated with the development of atherosclerosis. Although the mechanism is not fully illustrated, the inflammatory responses play an important role. The present study aimed to explore whether PM2.5 -exacerbated atherosclerosis was mediated by the cooperation of cluster of differentiation 36 (CD36) and nucleotide-binding oligomerization domain-like receptor protein (NLRP3) inflammasome in apolipoprotein E -/- (ApoE -/- ) mice. Thirty-two ApoE -/- mice were randomly divided into two groups. One group was fed with high fat chow (HFC) for 10 weeks to establish atherosclerotic model, and the other was fed with normal chow (NC). From week 11, the mice were exposed to concentrated PM2.5 (PM) or filtered air (FA) using Shanghai Meteorological and Environmental Animal Exposure System for 16 weeks. In both NC and HFC groups, PM2.5 exposure induced the formation of atherosclerosis plaque. Similarly, PM mice appeared higher lipid content in the aortic root than that in the FA mice. Compared with the FA mice, PM mice appeared a decrease in high density lipoprotein-cholesterol (HDL-C) and apolipoprotein A1 along with an increase in apolipoprotein B, low density lipoprotein-cholesterol (LDL-C) and oxidized low-density lipoprotein (ox-LDL). Moreover, PM2.5 exposure induced increase of CD36 in serum and aorta. In both NC and HFC groups, NLRP3 inflammasome activation-related indicators were activated or increased in the aorta of the PM mice when compared with the FA mice. The cooperation of CD36 and NLRP3 inflammasome activation may be the potential mechanisms linkixposed to concentrated PM2.5 (PM) or filtered air (FA) using Shanghai Meteorological and Environmental Animal Exposure System for 16 weeks. In both NC and HFC groups, PM2.5 exposure induced the formation of atherosclerosis plaque. Similarly, PM mice appeared higher lipid content in the aortic root than that in the FA mice. Compared with the FA mice, PM mice appeared a decrease in high density lipoprotein-cholesterol (HDL-C) and apolipoprotein A1 along with an increase in apolipoprotein B, low density lipoprotein-cholesterol (LDL-C) and oxidized low-density lipoprotein (ox-LDL). Moreover, PM2.5 exposure induced increase of CD36 in serum and aorta. In both NC and HFC groups, NLRP3 inflammasome activation-related indicators were activated or increased in the aorta of the PM mice when compared with the FA mice. The cooperation of CD36 and NLRP3 inflammasome activation may be the potential mechanisms linking air pollution and HFC-induced atherosclerosis even in the mice with NC intake.